Uma avaliação do programa de DST/AIDS do município do Rio de Janeiro: a ótica dos atores sociais - Freitas, Letícia Silva de Oliveira (1999)
Evoluation of the DST/AIDS program of Rio de Janeiro city. The research has in view the identification of the perceptions, expectations and suggestions about the abovementioned program, from the optic of the users, health professionals and unit coordinators, concerning the quality of the offered services. The study theorical and methodological options are based on the hermeneutical and dialectical bording, since it searches for the analyses of the social meanings. Owing to the fact that this theme is deeply complex, it gives priority to the qualitative methodology in the collect and in the data treatment, considering that the bording allows an approach and sinking of the phenomenon comprehension. It gives the prerrogative of the research in a descriptive and analytical way. The field research occurs in a municipal health center and in an AIDS Anonimous Testing Center, both located in Rio de Janeiro, who offer ambulatorial and testing services, giving emphasis to the prevention. To rescue the actors' speech, a half-structured interview was used. The research focus the social actors' optic on the assistence which is given. The empirical material analysis indicates that the quality of the services offered by the DST/AIDS program in town is efficient regarding the ways which were taken in the work development. However, regarding the human resources and materiais, some limitations occur when needed a range for efficacy and a effective impact, in the point of view of the behaviour change and the epidemy control in Rio de Janeiro city. This problematic points to a reconstruction of the directives, budgetary and technical politics and, principally, of a more effective media joined to the population who use the services and to the professionals, who develop the program activities, in order to listen and discuss their demands, what will fali into a contribution to conduct the program